The use of radiolocation control methods to protect the perimeters of large objects - Kolisnyk, Kostyantyn Vasilevich; Kipensky, Andrey Vladimirovich; Sokol, Yevgen I. (National Aviation University, 2012)
To detect an intruder for the perimeter security of a large object it is proposed to use radiolocation sensors. The sensors are chosen with taking into account the use conditions, which are inhomogeneous along the object perimeter. The way to simplify a synthesis of the security system is to use a space imaging data.
Keywords: radiolocation control systems; perimeters protection control; electronic devises; quality assurance